Study on the Optimization of Eddy Current Testing Coil and the Defect Detection Sensitivity. (2015) - Zhou, H.T.; Hou, K.; Pan, H.L.; Chen, J.J.; Wang, Q.M.
Abstract: As an essential component in the eddy current testing system, the detection sensitivity of eddy current probe affects the performance of the system. Different probes such as cylindrical differential probe, single orthogonal rectangular probe and biorthogonal rectangular probe were modeled using Comsol Multiphysics in this paper. The electromagnetic characteristics of probes were analyzed through the finite element simulation. Comparing the different probe detection signals, the new biorthogonal rectangular probe was found to have a better inhibition effect on the lift-off effect. The detection capability of probes according to flaw's width, length and depth were also studied. Based on the results of simulation, a new type of biorthogonal rectangular probe with higher detection sensitivity was designed.